A Geochemical Proxy for Recognizing Sequence Stratigraphic Surfaces in Late Cretaceous Sediments of Ariyalur Area, Cauvery Basin, South India - Nagendra, R.; Bakkiaraj, D.; Nagarajan, Ramasamy; Reddy, A. (Gondwana Geological Society, University of Nagpur, 2010)
The geochemical tool is employed to recognize the sequence stratigraphic surfaces of the Campanian-Maastrichtian sediments of the Ariyalur area in the Cauvery Basin. The Sillakkudi Formation (Campanian) underlies the Kallankurichchi Formation of Maastrichtian age. The sequence stratigraphic surfaces are recognised by employing the major and trace elements. The high ratio of Mn/Al concentrations confirms the relative rise of sea-level and the Mn Maxima coincides with biostromal limestone, which marks the MFS in the outcrop section. The TST and MFS in both Sillakkudi and Kallankurichchi Formations are recognized by the positive digressions in Ti/Al. The sequence boundaries are identified based on the low trends Ti/Al and Zr/Al chemical contents. The high Ti/Al ratios in the Sillakkudi sandstone are derived from the increased siliciclastic supply, and the low values of Ti/Al in the Maastrichtian limestones are derived from the non-siliciclastic supply.